2014
DOI: 10.14740/ijcp164w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Echocardiography as a Marker of Cardiovascular Risk in Obese Children and Adolescents

Abstract: Background: Childhood obesity is a global epidemic and its prevalence has increased from the early 1970s to the 1990s. The objective of the study was to compare the echocardiographic parameters of left ventricular (LV) geometry between obese and non-obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…4 Additionally, studies suggest that maintenance of obesity is directly associated with morbidity and mortality from cardiovascular diseases. [5][6][7][8][9] In Brazil, the Ministry of Health's strategic action plan for non-transmissible chronic diseases (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022) states that the prevalence of overweight among children aged 5 to 9 years has reached 33.5%, while obesity in the same age group has reached 14.3%, according to the Brazilian Institute of Geography and Statistics (IBGE -Instituto Brasileiro de Geografia e Estatística). 10,11 In the 10 to 19 years age group, the prevalence of overweight among adolescents was 20%, while the prevalence of obesity was 4% among girls and 5.9% among boys.…”
Section: Introductionmentioning
confidence: 99%
“…4 Additionally, studies suggest that maintenance of obesity is directly associated with morbidity and mortality from cardiovascular diseases. [5][6][7][8][9] In Brazil, the Ministry of Health's strategic action plan for non-transmissible chronic diseases (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022) states that the prevalence of overweight among children aged 5 to 9 years has reached 33.5%, while obesity in the same age group has reached 14.3%, according to the Brazilian Institute of Geography and Statistics (IBGE -Instituto Brasileiro de Geografia e Estatística). 10,11 In the 10 to 19 years age group, the prevalence of overweight among adolescents was 20%, while the prevalence of obesity was 4% among girls and 5.9% among boys.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma and obstructive sleep apnea are linked to obesity, which is related to a higher risk of pulmonary infections [ 66 ]. Cardiac anatomy changes, higher blood pressure and medications [ 67 ], intima layer artery thickening [ 68 ], endothelial dysfunction, and damage to the endothelium due to leptin perivascular adipose tissue have been explained in obese children. In obese individuals, chronic inflammation impairs the regulation of anticoagulant factors that contribute to venous thromboembolism during COVID-19 [ 69 ].…”
Section: Obesitymentioning
confidence: 99%
“…Regarding the heart, we investigated if obese children, with ages between 6 and 9 years, has detectable modifications of the heart anatomy, especially regarding to the left ventricle, and we found that, among 5 index evaluated, two of them (the LV mass and the LV3 index) showed differences, with greater thickness of the ventricle among obese children [4]. The intima-media complex of common carotid artery can be accessed using ultrasonography.…”
Section: Opinionmentioning
confidence: 99%
“…The prevalence was very high, independently of the method: 33.1% using fasting insulin > 15 and 37.8% using HOMA> 3.5 [1]. We also looked at blood pressure and we showed high blood pressure values among obese children, when compared to eutrophic children [3][4][5].…”
Section: Opinionmentioning
confidence: 99%